Imaging of Usual and Unusual Complication of Rotator Cuff Repair. Issue 3 (May 2019) - Albano, Domenico; Chianca, Vito; Zappia, Marcello; Russo, Raffaele; Romano, Stefania; Sconfienza, Luca Maria; Di Pietto, Francesco
Abstract : Abstract: Several complications may be encountered after rotator cuff (RC) repair. A thorough knowledge of surgical interventions, normal postoperative findings, and postoperative complications is crucial to provide a timely diagnosis, improving the clinical outcome of patients. Postoperative complications may involve RC, implanted device, osteochondral tissue, surgical-site infection, peripheral nerves, soft tissues, and vascular structures. In this review, we discuss the usual and unusual complications detectable after RC repair.